ANALYSIS OF FACTORS FOR STUDENTS' VOCABULARY MASTERY IN ENGLISH AT SMPN 35 MAKASSAR - Rianti, Rianti; Batau, St. Haliah; Muliati, Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
The objective of the research was to find out the factors that influence the English vocabulary mastery of the second grade of SMPN 35 Makassar. This research method is descriptive quantitative research method. This research was conducted on the second-grade students of SMPN 35 Makassar. The sample in this study were 20 students in class VIII-1 for the 2023/2024 academic year. The researcher analyzed data from questionnaires which distributed to students using quantitative descriptive analysis with the percentage of information frequency divided by the number of samples. The finding reveals that there were two factors that influence to students' vocabulary mastery namely, internal factors and external factors. The Internal factors is the most dominant factors influencing to students' vocabulary mastery. These internal factors consist of two, namely students' motivation to learn vocabulary and students' self-confidence in learning vocabulary. External factors are factors that influence students from outside in mastering vocabulary. These external factors consist of the family environment and the school environment. Keywords: Factors, Mastery, Students’ Vocabulary